2010
DOI: 10.1523/jneurosci.2197-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Insular Cortex Activity Is Associated with Effects of Negative Expectation on Nociceptive Long-Term Habituation

Abstract: It is generally accepted that acute painful experience is influenced by context information shaping expectation and modulating attention, arousal, stress, and mood. However, little is known about the nature, duration, and extent of this effect, particularly regarding the negative expectation. We used a standardized longitudinal pain paradigm and painful heat test stimuli in healthy participants over a time course of 8 consecutive days, inducing nociceptive habituation over time. Thirty-eight healthy volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 29 publications
3
66
0
3
Order By: Relevance
“…Previous behavioral and neuroimaging studies have shown that these responses to repetitive noxious stimulation involve central nervous system mechanisms, such as activity in the descending pain modulatory system, 4,42 are modulated by both bottomup and top-down factors, such as expectation, 28 and might be associated with the individual's susceptibility to clinical pain disorders. 11,24,35,40 However, in most of these studies on habituation and sensitization, painful heat stimuli were applied to the extremities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous behavioral and neuroimaging studies have shown that these responses to repetitive noxious stimulation involve central nervous system mechanisms, such as activity in the descending pain modulatory system, 4,42 are modulated by both bottomup and top-down factors, such as expectation, 28 and might be associated with the individual's susceptibility to clinical pain disorders. 11,24,35,40 However, in most of these studies on habituation and sensitization, painful heat stimuli were applied to the extremities.…”
mentioning
confidence: 99%
“…11,24,35,40 However, in most of these studies on habituation and sensitization, painful heat stimuli were applied to the extremities. 4,6,21,28,39 Only a few studies have investigated habituation to repetitive pain stimuli in the trigeminal system, 1,36,37 and they did not directly compare habituation and sensitization processes between the trigeminal and spinal systems (limb).…”
mentioning
confidence: 99%
“…The role of negative perceptions and attitudes were previously described and are known to have the potential to negatively impact adherence and treatment outcomes [8][9][10]. Different publications have described this as the nocebo effect, which is the negative equivalent to a placebo effect, and have looked into its impact on adherence to medications [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research suggests that higher cognitive processes influence the extent of habituation to noxious stimulations. Habituation in healthy adults can be attenuated when they are informed that noxious stimulus levels may intensify over time [17], whereas expectation of attenuated stimulus levels over time seems to potentiate habituation [18].…”
Section: Introductionmentioning
confidence: 99%